Using Dyestuff Obtained from Turkish Red Pine Bark Combined with Cationic Starch in Paper Dyeing - Ayhan Gençer; Cengiz Keşmer; Ayben Kiliç Pekgözlü; Mehmet Bebekli; Ahmet Can; Esra Ceylan (Drvna Industrija)
This study will be important in reducing water pollution, especially by not using chemical agents in the dyeing process and using organic mordant in the paper dyeing process. The cationic starch (CS) is also used as a mordant. CS increases the dry strength properties of the paper as well as the dye adhesion, and it is important in terms of providing two functions to an additive at the same time. In this study, natural dyestuff was obtained from Turkish red pine (Pinus brutia Ten.) bark by boiling in water, and bleached eucalyptus pulp was dyed. CS, which can increase the paper dry strength, was used as a mordant in the dyeing process. CS was mixed with distilled water in a hot water bath at (95±2) ºC and gelled. Thanks to 1.5 % CS addition, the tensile index increased by 38 %. With the addition of dyestuff, the papers became red and yellow. Adding CS and increasing the amount of dyestuff darkened the tone of these colors. However, CS addition was more effective than increasing the amount of dyestuff. That is to say, increasing the amount of dye alone in CS-free papers was not as effective as in CS-added papers.